Wireless Power Delivery Techniques for Miniature Implantable Bioelectronics. Issue 17 (10th June 2021) - Singer, Amanda; Robinson, Jacob T.
Abstract: Progress in implanted bioelectronic technology offers the opportunity to develop more effective tools for personalized electronic medicine. While there are numerous clinical and pre‐clinical applications for these devices, power delivery to these systems can be challenging. Wireless battery‐free devices offer advantages such as a smaller and lighter device footprint and reduced failures and infections by eliminating lead wires. However, with the development of wireless technologies, there are fundamental tradeoffs between five essential factors: power, miniaturization, depth, alignment tolerance, and transmitter distance, while still allowing devices to work within safety limits. These tradeoffs mean that multiple forms of wireless power transfer are necessary for different devices to best meet the needs for a given biological target. Here six different types of wireless power transfer technologies used in bioelectronic implants—inductive coupling, radio frequency, mid‐field, ultrasound, magnetoelectrics, and light—are reviewed in context of the five tradeoffs listed above. This core group of wireless power modalities is then used to suggest possible future bioelectronic technologies and their biological applications. Abstract : Six different types of wireless power transfer technologies used in bioelectronic implants—inductive coupling, radio frequency, mid‐field, ultrasound, magnetoelectrics, and light—in the context of five fundamental tradeoffs: power, miniaturization, depth, alignment tolerance, and transmitter distance are reviewed. Then possible future bioelectronic technologies and their biological applications for these wireless power modalities are suggested.